399 Surgical morbidity of the retroperitoneal staging in patients undergoing surgery for early stage epithelial ovarian cancer. (13th November 2020) - Dri, M; Lembo, A; Longo, M; Oltolina, N; Riva, M; Artuso, V; Ghezzi, F; Casarin, J
Abstract : Introduction: Surgery is the cornerstone of the apparent early stage ovarian cancer (aEOC) treatment. For the purpose of this study we evaluated perioperative outcomes and 30-days surgical morbidity of the retroperitoneal staging in patients undergoing surgery for aEOC. Methods: This is a retrospective single-center observational study conducted at Del Ponte Hospital of Varese (Italy) between January 2000 and December 2019. We included consecutive patients who underwent surgery for aEOC over the study period. Women who had a fertility-sparing approach were excluded. The cases were stratified into two groups: lymph node dissection performed (LND) and not-performed (NO-LND). We compared surgical outcomes (operative time, blood loss, need for blood transfusions) and complications within 30 days from surgery (stratified as follows: intra-operative, in-hospital, post-discharge, non-surgical). Results: Overall 109 patients were included: 71 (65, 45%) and 38 (34.86%) in LND and NO-LND groups, respectively. No differences were found in terms of baseline characteristics between the groups. Surgical approach was laparoscopic in 95 patients (87.16%) and open surgery in 14 (12.84%). Median operative time was 325 min (240–390) for LND and 135 (170–200.5) for NO-LND (p<0.001). No significant differences between the groups were found in terms of blood loss, transfusion rates and complications. Conclusions: The execution of systematic lymphadenectomy for aEOC was associated with prolonged operative time. However, in a referral center for minimally invasive surgery, the retroperitoneal staging did not influence the overall surgical morbidity.